A critical analysis of the Kiba (song-dance-drama) discourse - Galane, Sello (African Languages and Literatures, 2023)
1 Aim The aim of the research is to map out the theoretical construct of Kiba from practice. The analysis includes the mapping out of the metalanguage of the theory used by its practitioners. Therefore the research will map out a theory of Kiba not as a generic hypothetical theory of music and dance, but as a theory that describes actual performance. The research aims to achieve this not only through the description of what practitioners do in actual performance, but also through analysing the language behaviour and principles that govern the making of the performance discourse. The research will also look into the dynamic nature of culture and the challenges of ownership and rights that emerge. The analysis starts by tracing social practices and ethics that influence dance, drumming, music making, praise, and design of costume used in contemporary Kiba. It also looks at compositional structures, aesthetic elements, and principles governing the communicative competence of Kiba. The research presents the texts in Sepedi with English translations. It focuses on the description and analysis of principles governing the production and management of the discourse. Though the analysis focuses on the communicative function and value of Kiba, its main thrust is on principles that govern the making of the integral communication. The researcher uses mainly the performers' interpretation of the Kiba performance theory, as well as approaches to the analysis of cultural context of communication espoused by Hymes (1970) and Saville-Troike (1989). 2 Hypothesis If Kiba practice theory is not developed, then Kiba will not find access into the mainstream of Arts and Culture curricula at all levels of education. The chances of it competing successfully in economic markets of the Arts and Culture will not see the light of day. 3 Methods and procedures Kiba is a complex genre. The analysis of its performance discourse, that is, its dance-drama and praise-song of Kiba requires an interdisciplinary approach. This will be particularly useful in the analysis of the dance sequence structure with its dramatic effect, and of the principles governing the choices of repertoire and music elements. Barber (1989:13) supports this approach for the analysis of complex genres. She points out that: There is an obvious and very good reason for taking an interdisciplinary approach to African oral texts, and that is that the texts themselves can combine 'literature', 'history', 'music', 'religion' and other things. The unity of these fields within oral texts suggests that the method of interpretation should also be unified. Rather than collaboration between specialists from different disciplines, what is needed is the reintegration of an artificially divided field. It is crucial to state from the outset that the research does not perceive Kiba as music or art, but as a way of lived communication and it echoes the observation made by Agawu (2002: 452) that: ... in many African languages, there is no single word for 'music' that the term is semantically dispersed across many fields often indexing dancing or movement as well as the actual sound produced. However, since the overall vehicle of a Kiba performance is presented in songdance, the research will trace the 'musical' and not the 'music' elements of Kiba. Nevertheless it does make a conscious effort to strike a balance between the musical, literary, dance, and the philosophical. iii In Sepedi as well as the broad Sotho languages, the word for music is 'mmino'. This refers to both song and dance. This concept will be represented in the research as 'song-dance'. Therefore, a multidisciplinary approach to the study of Kiba will prove to be more useful than an approach to music or just dance elements of Kiba. An analysis of the co-operative principles that underpin the Kiba discourse, and the cultural and compositional elements of Kiba will form part of the interdisciplinary approach to the study of Kiba. The research will also use elements of sociolinguistics, cantometrics, ethnomethodology and ethnomusicology to analyse Kiba discourse. iv 4 Procedures: focus areas of the research The entire inquiry obtained data from participants through unstructured interviews and observation of the language behaviour of Kiba interlocutors. Observation and interviews were carried out in ten villages. The basic questions and the researcher's observation of live performance of Kiba focused on the three main areas of the research: compositional structure, aesthetic elements, and principles governing the actual performance. The latter refers to the norms and standards of interaction in, and interpretation of, Kiba discourse. The basic questions that are asked are: Definition of Kiba □ Kiba ke eng?I What is Kiba? ✓ A Kiba ke ya banna goba ke ya basadi?l ls Kiba a male or female genre? ✓ A Kiba ke ya baswa goba ke ya batho ba bagolo? /Is Kiba a youth or adult genre? Compositional and aesthetic elements: □ Ge le bina Kiba le dira eng? I What are the structural elements of Kiba? □ Mekgwa ya go natefisa kosa ke efe? /What are the ways of embellishing a song? □ Diletso tse di diriswago mo Kibeng ke dife? I What resources are used in the Kiba communication system? Which principles govern actual performance communication? Examine the following: □ Poledisano le kgolagano ya kosa magareng a malokwane le sehlopha, le magareng ga sehlopha le babogedi goba setshaba? I The discourse structure of the Kiba intra-communication system: analysis of the intercommunication strategies between the Kiba participants as addressers and an individual or a community as addressee(s). V □ A Kiba ke ya Bapedi goba ke Sepedi? Is Kiba a genre of the Bapedi or is it Sepedi? Translated texts appear beneath the original texts. Original texts appear in italics, while translations are typed in normal font as Mason (interview: Washington DC, June 1997) advises. Vernacular names and words are used and explained in context. Single word expressions and exclamations have been retained and their explanations are given in square brackets. A glossary of terms has been provided at the end of the thesis. 5 Abbreviated thesis Accompanying the research is an audio-visual presentation that shows the · prototype of an integral and fully expanded discourse of Kiba. The video is intended to help the reader and viewer to understand performance nuances of dance, drumming, voice technique, and the use of colour. The audiovisual excerpt of an exemplary performance of Kiba is provided as annexure 4. The latter is an authentic text that shows a royal ensemble, led by Chief Ramokgopa during his official visit to the royal capital of Moletsi on 1 January 1999. The excerpt shows every aspect of Kiba raised by the research. vi There are also accompanying compact discs, which reveal the conscious attempt to further develop Kiba into a modern competitive format called FreeKiba. (See the copies of the themes presented in annexure I, and the two CDs that are provided as part of annexure 4). Agawu (2002:47) perceives this kind of an adaptation as progressive in that it is premised on the agenda of the emancipation of African music. He puts it succinctly: The emancipation of African music begins precisely at the point where our priorities shift from valuing present realities to constructing future possibilities. This view is also held by Nzewi (1980, 1983). 6 Conclusion The research will use ethnomusicology to analyse participants' use of song, dance, drama, drumming and praise-singing as integral constituents of Kiba. To analyse the Kiba discourse structure, the research will use the 'ethnography of communication method. The method is useful in the analysis principles governing the appropriateness of lived communication (Hymes 1964). It also requires principles of ethnomethodology to be used to 'discover what methods [Kiba] practitioners use to participate in and make sense of interactions of their